Viz-Blocks: Building Visualizations and Documents in the Browser - McNeill, G; Hale, S (Eurographics Association, 2019)
Viz-Blocks is a simple browser-based UI for data exploration and document creation. It incorporates the Vega-Lite grammar of graphics for standard visualizations (including multiple views and interaction) whereas 'code blocks' provide the full power of the JavaScript ecosystem for creating custom visualizations and other bespoke content. Visualizations are treated as reusable 'blocks' that are easily created, modified and compared during exploration. When preparing results for dissemination, visualizations can be customized and combined with Markdown and image blocks to produce a single or multi-page HTML document that is easily styled and exported. Viz-blocks was designed in consultation with academics, students and policy makers to bridge the gap between visualization tools and more traditional document-authoring tools. The application is aimed at a wide audience: the lightweight, hybrid UI allows all users to access the core functionality, while experienced users can take advantage of code-blocks and the option to use advanced features of Vega-Lite via JSON/YAML snippets.